Desolate public space - Páramo, Pablo; Burbano, Andrea (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
This research article presents the direct experience of transformations observed in urban public spaces during the period of lockdown in which citizens from different cities of the world were constrained as a measure adopted by governments to prevent the spread of COVID-19. After considering the public space, a setting of democratic expressions for the revindication of social movements, demonstrations of political tension, exhibitions of artistic expression and the fulfillment of human needs such as socialization, recreation and sport, it is now desolate. It discusses the implications of the imposed regulations on democracy, freedom of expression and movement, and particularly on the socialization, the personal distances, recognition of faces, sounds of the streets and the redirection of the interests of investigators of public life. It warns of the long-term changes that the effect of isolation may have on how we use public spaces in our social lives in the future, even once the pandemic has been contained.